Предмет доказування у справах щодо захисту сімейних прав та інтересів дитини у цивільному судочинстві - Волкова, Наталія Василівна; Волкова, Н. В.; Volkova, Nataliia V. (Херсон : Видавничий дім «Гельветика», 2019)
Стаття присвячена дослідженню предмета доказування у справах щодо захисту сімейних прав та інтересів дитини. З урахуванням аналізу норм національного законодавства, основних доктринальних підходів та правозастосовної практики, визначено і проаналізовано предмет доказування у справах про визначення місця проживання дитини, про позбавлення батьківських прав, про визнання та оспорювання батьківства.

The article is devoted to the research of the subject of proof in cases of protection of the family rights and interests of the child. Taking into account the analysis of the norms of the national legislation, the basic doctrinal approaches and the law enforcement practice, the subject of proving in the cases of determining the place of residence of the child, deprivation of parental rights, recognition and contestation of paternity and the like have been identified and analyzed. The correct determination of the subject-matter of the evidence is very important, since not finding out the material circumstances of the case entails the adoption of an unlawful and unjustified court decision, and not to achieve the objective of civil justice, which provides for the effective protection of the violated, unrecognized or contested rights, freedoms or interests of individuals, rights and interests of legal entities and interests of the state. The incorrect determination of the circumstances of the case is the basis for challenging the decision of the court. In most cases concerning the protection of the family rights and interests of the child, the subject of proof is the circumstances (facts) determined by the rule (or rules) of substantive law upon which the case will be decided. Sometimes, the rule of law does not specify the facts that have certain legal consequences, but only general features and features. Therefore, courts, especially in child-rearing cases, often face some difficulties. This applies, in particular, to cases involving parental disputes and cases involving parental or other persons concerning the transfer or abandonment of a child to one party. The sheer complexity of parental action in the upbringing of children does not make it possible to fully disclose in law the content of parental rights and responsibilities. Therefore, the subject matter of the case for the protection of the family rights and interests of the child includes circumstances (facts) which confirm the stated claims or objections or have other significance for the consideration of the case and are subject to determination in the court decision.
Волкова Н. В. Предмет доказування у справах щодо захисту сімейних прав та інтересів дитини у цивільному судочинстві / Н. В. Волкова // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Херсон : Видавничий дім «Гельветика», 2019. – Вип. 34. – С. 36-39.
Keywords: предмет доказування; захист сімейних прав та інтересів дитини; позбавлення батьківських прав; визнання та оспорювання батьківства; цивільне судочинство; subject of proof; protection of the family rights and interests of the child; deprivation of parental rights; recognition and contesting paternity; civil proceedings; Research Subject Categories::LAW/JURISPRUDENCE